HUBUNGAN POLA KONSUMSI INHIBITOR, ENHANCER ZAT BESI DAN FAKTOR LAINNYA DENGAN KEJADIAN ANEMIA REMAJA PUTRI DI SMPN 2 GUNUNGSINDUR BOGOR - Alifiah, Nursyifa; Sugiatmi, Sugiatmi (Jurnal Gizi dan Pangan Soedirman, 2024)
Anemia is a significant nutritional issue faced by many developing countries, including Indonesia. Anemia can lead to decreased concentration and developmental disorders, negatively impacting the academic performance and quality of life of adolescent girls. This study aims to analyze the relationship between inhibitor and enhancer iron consumption patterns and other factors with the occurrence of anemia in adolescent girls at SMPN 2 Gunungsindur Bogor. This research is quantitative research with the design of a cross-sectional study. The sample consisted of 72 adolescent girls selected through proportional simple random sampling. The data analysis was conducted with univariate tests and bivariate test with Chi-square. The Result found the prevalence of anemia among adolescent girls at SMPN 2 Gunungsindur was 43.1%. The study found significant relationships between anemia occurrence and consumption patterns of inhibitor iron (p=0,000), consumption patterns of enhancer iron (0,000), nutritional status (p=0,000), knowledge about anemia (p=0,023), and family income (p=0,024). Therefore, additional efforts is needed to increase awareness and knowledge among adolescent girls about anemia by implementing healthy dietary behavior and paying attention to adequate nutritional intake.